Pengaruh Percaya Diri dan Tekad Yang Kuat Terhadap Berwirausaha - Formaida Tambunan; Renika Hasibuan (Jurnal Administrasi Publik (Public Administration Journal), 2018)
The purpose of this research is to know the influence of confidence and determination towards entrepreneurship. The data in this study consists of primary data obtained through questionnaires while the secondary data obtained through the village new terrain Medan Denai. The data obtained are then processed and analyzed with statistical test of Chi-Square in order to be retrieved if there is influence of confidence and determination towards entrepreneurship. The results showed: 1) majority of Entrepreneurship with the category both as much as 48 (52.7%) and the category less obtained 43 (47.3%), 2) the confidence of the majority of the categories less as much as 47 (51.6%) and the category strong retrieved 44 (48.4%), 3) the determination of the majority with a low category as many as 57 (62.6%) and higher category obtained 34 (37.4%), 4) confident effect on entrepreneurship with a value of p = 0.000. 5) determination to entrepreneurship with the value p = 0.028. Of research results obtained then expected society that entrepreneurship can instill a strong determination and has high confidence in entrepreneurship as well as Assistant researchers furthermore expected to be developed by adding some of the variables. It is based on that there are several factors that affect entrepreneurship.